AN ETHNOMATHEMATICAL STUDY ON CONTEMPORARY VASE AS AN INSPIRATION OF BATIK DESIGN - Wan Norliza Wan Bakar; Junaidi Awang; Muslim Ismail; Saipudin Hasbullah (Journal of Islamic, Social, Economics and Development, 2023)
A contemporary vase is a container designed to hold flowers which draws inspiration from traditional or classic vases but expresses creativity through its use. Contemporary vase can be an inspiration for batik design because of its shapes are unique and commonly accepted. This study focuses on the ethnomathematical study on contemporary vase focusing on their shapes as an inspiration of batik design. This research was qualitative research with an ethnographic approach. Data obtained through observation, interview, literacy study and documentation, with the triangulation method as data validity. This research examined the mathematical concepts of contemporary vase shapes as an inspiration of batik design. Six different types of vases were selected. Based o the result of the study, it was found that there were mathematical concepts found.